Strategi Dakwah PAC IPNU IPPNU dalam Mencegah Kenakalan Remaja di Kecamatan Siliragung, Kabupaten Banyuwangi - Azizah, Noviatul; Suma, Nasobi Niki (Fakultas Dakwah UIN KHAS Jember, 2023)
The problem of juvenile delinquency that occurs in Siliragung District in particular causes concern for parents or the community. This requires da'wah to build good morals in the process of adolescent growth and development. The focus of research in this thesis is: 1) What are the cases of juvenile delinquency in Siliragung District, Banyuwangi Regency? 2) What is the da'wah strategy of PAC IPNU – IPPNU in preventing juvenile delinquency in Siliragung District, Banyuwangi Regency? 3) What are the supporting and inhibiting factors for the PAC IPNU – IPPNU da'wah strategy in preventing juvenile delinquency in Siliragung District, Banyuwangi Regency? The aim of this research is to describe cases of juvenile delinquency in Siliragung District, to find out the da'wah strategies used by the IPNU-IPPNU PAC in preventing juvenile delinquency, as well as the supporting and inhibiting factors experienced by the IPNU-IPPNU PAC. This research uses a descriptive qualitative approach, with data collection techniques using interviews, observation and documentation. This research came to the conclusion that: 1) Juvenile delinquency cases are grouped into three, namely ordinary delinquency, delinquency that leads to violations, and special delinquency. 2) The da'wah strategies used, namely sentimental strategies and rational strategies. 3) There are supporting and inhibiting factors from internal and external to the organization.